The multiple activities of BAG3 protein: Mechanisms - Marzullo, Liberato; Turco, Maria Caterina; De Marco, Margot (Biochimica et biophysica acta. General subjects, 2020)
BAG3 was identified as a co-chaperone of the heat shock protein (Hsp) 70, which helps, through the binding to the ATPase domain, the ADP release from the chaperone and the nucleotide cycling. By interacting with Hsp70, BAG3 modulates the activities of this chaperone, including the delivery of client proteins to proteasome. BAG3 can also carry out Hsp70- independent functions, through its interactions with other proteins involved in apoptosis, cytoskeleton dynamics and other pathways. Here we provide a summary of the main mechanisms which encompass BAG3 as an intracellular factor involved in different pathways which regulate and modulate the physiological cell response. Furthermore, it has been shown that BAG3 can be secreted by some cell types and is able to activate the monocytes through the binding on a membrane cell receptor, indicating that the protein can act like an alarmin with different functions inside and outside the cell. Whereas intracellularly BAG3 sustains the levels of anti-apoptotic factors and other molecules, participates in protein quality control, drives the cytoskeleton dynamics, exerts structural and functional roles in myocytes, the discovery of a secreted BAG3 opened a new field of investigation in tumor development and progression, revealing its role in a new signaling pathway, mediated by the BAG3/BAG3R axis, which also includes monocytes and other stromal cells. BAG3 is a multifunctional protein that is involved cell stress response through its participation in several regulatory pathways which control cell homeostatic response in physiological and pathological conditions. •BAG3 protein modulates multiple pathways involved into cell stress response.•Apoptosis, autophagy, cytoskeleton dynamics are regulated by BAG3.•BAG3 supports cell survival in several tumor types under stressful conditions.•Recent advances reported a new paracrine activity of secreted BAG3 on macrophages.•BAG3/IFITM2 axis is a novel signaling pathway leading to tumor (PDAC) development.